Pengaruh Ekstrak Daun Salam (Eugenia polyantha, weight.) Sebagai Alternatif Mempertahankan Kualitas Daging - Ro Candra, Adhitya Yoppy; Yanestria, Sheila Marty; Mardijanto, Arief; Wibisono, Freshinta Jellia (VITEK : Bidang Kedokteran Hewan, 2022)
One of the good sources of animal protein comes from meat because it contains various kinds of nutrients needed by the body including protein, carbohydrates, water, vitamins, fats and various essential amino acids. The presence of high nutritional value in meat can also be utilized by various microorganisms to grow so that it can reduce the quality of meat. Some of these microorganisms can be transmitted to humans and cause disease or also known as zoonotic diseases. One way to prevent the growth of microorganisms in meat is by preserving meat using natural ingredients that can come from plants. One of the plants that has the potential to inhibit bacterial growth is Salam leaves (Eugenia polyantha, Weight.). The purpose of this study was to determine the value of the content in Salam Leaves (Eugenia polyantha, Weight.) and to determine the effect of giving Salam Leaf extract (Eugenia polyantha, Weight.) to early decay, pH value and Total Bacterial Colony. The study began with the collection of Salam leaves (Eugenia polyantha, Weight.) and then the extract was made. The extract obtained was then diluted and stored. The research was continued by taking meat samples from the Traditional Market in Surabaya and then cut into uniform sizes and soaked in Salam leaf extract with different concentrations. After incubation, the meat quality was tested for the beginning of spoilage, pH value and total bacterial colonies. The results of the observations showed that the best results were found in the P4 treatment with an extract concentration of 20%. This result is indicated by the lack of fog formed in the initial spoilage test, the pH value is close to the ultimate pH of the meat and a low total bacterial colony.